Plant litter functional diversity effects on litter mass loss depend on the macro-detritivore community - Patoine, Guillaume (Pedobiologia, 2017)
A better understanding of the mechanisms driving litter diversity effects on decomposition is needed to predict how biodiversity losses affect this crucial ecosystem process. In a microcosm study, we investigated the effects of litter functional diversity and two major groups of soil macro-detritivores on the mass loss of tree leaf litter mixtures. Furthermore, we tested the effects of litter trait community means and dissimilarity on litter mass loss for seven traits relevant to decomposition. We expected macro-detritivore effects on litter mass loss to be most pronounced in litter mixtures of high functional diversity. We used 24 leaf mixtures differing in functional diversity, which were composed of litter from four species from a pool of 16 common European tree species. Earthworms, isopods, or a combination of both were added to each litter combination for two months. Litter mass loss was significantly higher in the presence of earthworms than in that of isopods, whereas no synergistic effects of macro-detritivore mixtures were found. The effect of functional diversity of the litter material was highest in the presence of both macro-detritivore groups, supporting the notion that litter diversity effects are most pronounced in the presence of different detritivore species. Species-specific litter mass loss was explained by nutrient content, secondary compound concentration, and structural components. Moreover, dissimilarity in N concentrations increased litter mass loss, probably because detritivores having access to nutritionally diverse food sources. Furthermore, strong competition between the two macro-detritivores for soil surface litter resulted in a decrease of survival of both macro-detritivores. These results show that the effects of litter functional diversity on decomposition are contingent upon the macro-detritivore community and composition. We conclude that the temporal dynamics of litter trait diversity effects and their interaction with detritivore diversity are key to advancing our understanding of litter mass loss in nature